Beyond six billion : forecasting the world's population - Bongaarts, John, 1945-; Bulatao, Rodolfo A., 1944- (National Academy Press, 2000)
The National Academy Press (NAP) presents the full text of the 2000 book "Beyond Six Billion: Forecasting the World's Population." The book focuses on the projections that world population growth is slowing. The editors, John Bongaarts and Rodolfo A. Bulatao, investigate the reasons behind the projections, their accuracy, and how they can be improved.